Ips typographus and Dendroctonus ponderosae Models Project Thermal Suitability for Intra- and Inter-Continental Establishment in a Changing Climate - Bentz, Barbara J.; Jönsson, Anna Maria; Schroeder, Martin; Weed, Aaron; Wilcke, Renate Anna Irma; Larsson, Karin (Frontiers in Forests and Global Change, 2019)
Climate change is altering legacies of native insect-caused disturbances and contributing to non-native invasions globally. Many insect fitness traits are temperature dependent and projected climatic changes are expected to cause continued alterations in insect-caused tree mortality, with uncertain consequences for forest ecosystems and their management. Dendroctonus ponderosae in Pinus habitats of western North America and Ips typographus in European Picea are among the most significant tree mortality agents on each continent. Changing climate is influencing both species in their native habitats, although thermal suitability if they should invade new continents and novel forest habitats has not been investigated. We assessed thermal suitability for intra- and inter-continental establishment using physiological models that describe evolved, temperature-dependent traits of each species. Models were driven by projections from two Global Climate Models representing RCP 8.5. Simulations suggest that for both species the common phenological strategy of one generation annually (univoltine) will shift northward with warming throughout this century. As optimum habitat for I. typographus univoltinism shifts northward, habitat supporting a 2nd generation, a historically common strategy in warm European Picea forests, expands on both continents. In contrast, a 2nd D. ponderosae generation has been historically rare due to traits that evolved for phenological synchrony in its cool native habitats. As thermal habitat for D. ponderosae univoltinism shifts northward, suitability for a 2nd generation is limited to the warmest Pinus forests on both continents. In the near future (2011-2040), models project extensive thermal suitability for inter-continental establishment of both species, highlighting the need for effective mitigation policies and continued monitoring at ports in an era of climate change and increasing global trade. Throughout the century, thermal suitability remains high for I. typographus population success on both continents, for D. ponderosae in warm areas of Europe, and for D. ponderosae expansion into novel North American Pinus habitats. Portions of the historical D. ponderosae range, however, are projected to become thermally unsuitable.